Immigrants' Residential Choices and their Consequences - Christoph Albert; Joan Monras (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2017)
This paper investigates the causes and effects of the spatial distribution of immigrants across US cities. We document that: a) immigrants concentrate in large, high-wage, and expensive cities, b) the earnings gap between immigrants and natives is higher in larger and more expensive cities, and c) immigrants consume less locally than natives. In order to explain these findings, we develop a simple quantitative spatial equilibrium model in which immigrants consume (either directly, via remittances, or future consumption) a fraction of their income in their countries of origin. Thus, immigrants not only care about local prices, but also about price levels in their home country. Hence, if foreign goods are cheaper than local goods, immigrants prefer to live in high-wage, high-price, and high-productivity cities, where they also accept lower wages than natives. Using the estimated model we show that current levels of immigration have reduced economic activity in smaller, less productive cities by around 3 percent while they have expanded the activity in large and productive cities by around 4 percent. This has increased total aggregate output per worker by around .15 percent.
Keywords: F22; J31; J61; R11; 330; Immigration; location choices; spatial equilibrium